Tinjauan Terhadap Sarana dan Prasarana Serta Tata Ruang di Kantor Perpustakaan dan Arsip Kabupaten Padang Pariaman - Sartika, Mitra Dewi; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purposes of this study were: (1) describe the situation and condition of the building, rooms, facielities and insfratucture and spatial planning in the office of disctrict libraries and archieves Padang Pariaman; (2) discribe constraints faced in meetingÂ  infrastructure and special planning in the office of disctrict libraries and archieves Padang Pariaman. Technique of analyzing data is done by describing the interview, describing the results of direct observation, data has been obtained in accordance with the theory discussed, conclusions, and reporting. The results of this study are as follows: (1) facilities and infrastructure awned by the library is not adequate; (2) the constraints be faced by libraries and archieves Padang Pariaman not funds for development. Keywords: library; facilities and insfratucture